Socio-Rhetorical Interpretation: Textures of a Text and its Reception - Gowler, David B. (Journal for the study of the New Testament, 2010)
The meaning of a text does not reside alone in the creative genius of its author; there is a complex correlation between a text and the contexts in which a text has been read and reread, including various dynamic interrelations between creator and contemplators, past and present. Vernon Robbins’s socio-rhetorical interpretation provides a powerful interpretive analytic to explore these dialogic interrelations among authors, texts and readers/interpreters. Correspondingly, studies of reception history, through their investigations of significant additional voices that join the heteroglossic chorus of interpreters, provide critical insights for more comprehensive socio-rhetorical analyses of texts. This article chronicles the birth and development of socio-rhetorical interpretation, introduces major components of a socio-rhetorical approach, and provides examples of how socio-rhetorical interpretation and reception history can mutually inform each other.